2021
DOI: 10.3389/fvets.2021.761742
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Resin Acid and Zinc Oxide on Immune Status of Weaned Piglets Challenged With E. coli Lipopolysaccharide

Abstract: With the ban of zinc oxide (ZnO) at high dosages in piglet diets in Europe by 2022, alternative nutritional solutions are being tested to support piglet immune defence during their weaning, the most critical and stressful moment of pig production. The present study evaluated the effect of zinc oxide (ZnO; 2,500 mg/kg diet) and resin acid concentrate (RAC; 200 mg/kg diet) on the immune defence of weaned piglets challenged with lipopolysaccharide (LPS). Piglets were challenged at days 7 and 21 post-weaning, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Zinc is an essential trace element to maintain various physiological functions of the body, which can help in the development of the gastrointestinal tract, modulating the immune response and antioxidant system, and thus affecting the growth and health of piglets ( 14 16 ). Numerous studies have demonstrated that supplementing weaned piglet diets with pharmacological doses of ZnO could alleviate weaning stress and improve growth performance ( 3 , 17 , 18 ). However, the results of this study showed that dietary supplementation of 1600 mg Zn/kg from ZnO failed to improve the growth performance of piglets, which was consistent with the results reported by Mavromichalis et al ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Zinc is an essential trace element to maintain various physiological functions of the body, which can help in the development of the gastrointestinal tract, modulating the immune response and antioxidant system, and thus affecting the growth and health of piglets ( 14 16 ). Numerous studies have demonstrated that supplementing weaned piglet diets with pharmacological doses of ZnO could alleviate weaning stress and improve growth performance ( 3 , 17 , 18 ). However, the results of this study showed that dietary supplementation of 1600 mg Zn/kg from ZnO failed to improve the growth performance of piglets, which was consistent with the results reported by Mavromichalis et al ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Diarrhea is one of the consequences of gut inflammation and pathogenic toxins. Zinc oxide (ZnO) in concentrations higher than 1000 ppm is licensed as a veterinary medicinal product for the treatment and control of post-weaning diarrhea in swine [ 1 ]. Its importance has increased since the banning of in-feed antibiotics [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Investigation of the mechanism of action was beyond the scope of this trial, but in-depth analyses of biological samples in research incorporating singular and combined use of the two feed ingredients are recommended to provide further indications regarding the observed effects. The efficacy of TOFA in reducing F4-ETEC PWD may be derived from its antimicrobial 11 , 26 , anti-inflammatory 27 , immunomodulatory 13 , 28 and gut microbiome stabilizing properties 28 , 29 . The TOFA product used consisted of resin acids such as abietic, dehydroabietic and pimaric acids, as well as free fatty acids such as (conjugated) linoleic, oleic and pinolenic acids.…”
Section: Discussionmentioning
confidence: 99%
“…The resin acids of TOFA are lipophilic diterpene carboxylic acids with antimicrobial, antifungal and anti-inflammatory activities 8 11 . In previous in vivo studies, dietary TOFA was shown to improve performance and reduce PWD 12 and beneficially affect the immunological status of piglets 13 . Yeast and yeast derivatives are often used in farm animal diets because of their nutritional value and their positive effects on animal health and performance 14 16 .…”
Section: Introductionmentioning
confidence: 96%